Biomechanical analysis of transfemoral amputee's sprint running and block start - Ojala, Emilia (2012)
Ojala, Paula Emilia, 2012. Biomechanical analysis of transfemoral amputee’s sprint running and block start. Department of Biology of Physical Activity, University of Jyväskylä, Master’s Thesis in Biomechanics. 87 p.